OP66 Pathways between childhood socioeconomic position and standing balance performance at age 46: mediation analysis using the 1970 British Birth Cohort study. (26th August 2022) - Yusuf, Mohamed; McPhee, Jamie; Montgomery, Gallin; Cooper, Rachel
Abstract : Background: Poor standing balance is of great concern for falls in later life, and has been linked with disability, fractures, hospitalisations, and premature mortality. Existing studies have shown that lower childhood socioeconomic position (SEP) has been consistently linked with poorer standing balance in later life. However, the factors that may mediate these associations have not been investigated. We aimed to examine whether indicators of childhood SEP are associated with standing balance at age 46 and the extent to which any observed associations are mediated by factors in childhood and adulthood. Methods: Participants from the 1970 British Cohort study were included in analyses (N=7, 591). We used data on parental education levels and father's occupational class at age five; own occupational class, education level, weekly income after tax, housing tenure, BMI and height at age 46, as well as BMI, cognition and coordination ability at age 10, and health status at age 42. Height and sex-adjusted multinomial logistic regression models estimated the associations between childhood SEP and standing balance. Structural Equation Models were conducted to examine mediation; latent variables were constructed for childhood and adulthood SEP. Results: Participants with lower childhood SEP were more likely to attain a poor balance time and less likely to attain a high balance time than those with a higher SEP. For example, the adjusted relative risk ratio of achieving a time of less than 15sec with eyes open compared with a time of less than 15sec with eyes closed (reference group) was 2.56 (1.51, 4.32) when comparing father's occupational group V Unskilled with I Professional. The mediation model fitted well (Comparative Fit Index: 0.914; Root Mean Square Error of Approximation: 0.036). The association between childhood SEP and standing balance was fully mediated by the other factors included in the model; adulthood SEP (proportion mediated= 74.3%; 95% CI= 68.0, 80.6), adulthood BMI (10.4%; 7.4, 13.4), childhood cognition (8.9%; 4.6, 13.2), childhood coordination (3.0%; 1.1, 5.0), adulthood health status (2.3%; 0.4, 4.3), and childhood BMI (1.1%; 0.1, 2.1). Conclusion: Our findings add to previous studies by providing evidence of an association between lower childhood SEP and poorer balance performance at a younger age. The pathways tested show that these associations were explained by adulthood SEP, neurocognitive factors, health status and body size. Therefore, policies and interventions aiming to improve inequalities in balance outcomes in adulthood should consider these pathways.